Susceptibility of Clinical Enterobacterales Isolates With Common and Rare Carbapenemases to Mecillinam - Fuchs, Frieder; Ahmadzada, Aysel; Plambeck, Lars; Wille, Thorsten; Hamprecht, Axel (Frontiers in Microbiology, 2021)
Purpose: To investigate the susceptibility of carbapenemase-producing Enterobacterales (CPE) to mecillinam based on the recently updated EUCAST breakpoints for uncomplicated Urinary Tract Infection (uUTI). Methods: The challenge collection consisted of 105 molecularly characterized Enterobacterales (Klebsiella spp. (N=49), Escherichia coli (N=30), Enterobacter cloacae (n=13), Citrobacter freundii (N=9), Proteus mirabilis (N=3) and Raoultella ornithinolytica (N=1)). Isolates produced OXA-48 (N=18), OXA-48-like (N=18), VIM (N=22), NDM (N=22), KPC (N=12), IMI (N=9), IMP (N=6), GES (N=1), OXA-58 (N=2)) or combinations thereof (N=5). MICs of carbapenems were determined by agar gradient diffusion (AGD). MICs of mecillinam were assessed by agar dilution (reference method) and compared to disk diffusion (DD) and AGD. Results: Mecillinam was susceptible in 23/105 CPE (21.9 %) and susceptibility was observed in E. coli (N=12), E. cloacae (N=7) and K. pneumoniae (N=4) producing IMI, OXA-48, OXA-48-like and NDM-1 carbapenemases. MIC50 for mecillinam in all isolates was 128 mg/L while MIC50 for meropenem was 8 mg/L. Lower MICs for mecillinam were found in IMI (MIC50 8 mg/L) and OXA-48-like (MIC50 16 mg/L) producers. The comparison of the different susceptibility methods showed very major errors of 12.2% with AGD and 8.5% with DD when compared to the reference method. Conclusions: Mecillinam susceptibility was restricted to isolates producing IMI-, OXA-48-like and NDM-1 carbapenemases and was documented despite high carbapenem MICs in some isolates. Mecillinam could be a promising oral antimicrobial in uUTI caused by these CPE; however, susceptibility testing by AGD and DD remains problematic.